Les impacts de l'adhésion à la Communauté européenne sur la balance commerciale de l'Espagne et du Portugal - Éthier, Diane (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
This paper analyzes the entry into the European Community (EC) impacts on Spain and Portugal external Trade Balance (ETE). It points out that the dramatic increase of Iberian countries ETB deficit, since their adhesion to the EC, first January 1986, is mainly due to the strong growth of capital goods imports, in particular those from EC, in a context characterized by the gradual application of Customs Union mechanisms and the rise of internal demand. Then, it examines principal short and medium term measures susceptible to adjust Spain and Portugal ETB, especially restrictive economic policies and structural programs of modernization.